Genetics Adviser: a protocol for a mixed-methods randomised controlled trial evaluating a digital platform for genetics service delivery. Issue 4 (29th April 2022) - Shickh, Salma; Hirjikaka, Daena; Clausen, Marc; Kodida, Rita; Mighton, Chloe; Reble, Emma; Sam, Jordan; Panchal, Seema; Aronson, Melyssa; Graham, Tracy; Armel, Susan Randall; Glogowski, Emily; et al.
Abstract : Introduction: The high demand for genetic tests and limited supply of genetics professionals has created a need for alternative service delivery models. Digital tools are increasingly being used to support multiple points in the genetic testing journey; however, none are transferable across multiple clinical specialties and settings nor do they encompass the entire trajectory of the journey. We aim to evaluate the effectiveness of the Genetics Adviser, an interactive, patient-facing, online digital health tool that delivers pre-test counselling, provides support during the waiting period for results, and returns results with post-test counselling, encompassing the entire patient genetic testing journey. Methods and analysis: We will compare the Genetics Adviser paired with a brief genetic counselling session to genetic counselling alone in a randomised controlled trial. One hundred and forty patients who previously received uninformative genetic test results for their personal and family history of cancer will be recruited from familial cancer clinics in Toronto and offered all clinically significant results from genomic sequencing. Participants randomised into the intervention arm will use the Genetics Adviser to learn about genomic sequencing, receive pre-test counselling, support during the waiting period and results, supplemented with brief counselling from a genetic counsellor. Participants in the control arm will receive standard pre-test and post-test counselling for genomic sequencing from a genetic counsellor. Our primary outcome is decisional conflict following pre-test counselling from the Genetics Adviser+genetic counsellor or counsellor alone. Secondary outcomes include: knowledge, satisfaction with decision-making, anxiety, quality of life, psychological impact of results, empowerment, acceptability and economic impact for patients and the health system. A subset of patients will be interviewed to assess user experience. Ethics and dissemination: This study has been approved by Clinical Trials Ontario Streamlined Research Ethics Review System (REB#20–035). Results will be shared through stakeholder workshops, national and international conferences and peer-reviewed journals. Trial registration number: NCT04725565 .